The Quality of Cultural Services in the Global Economic Crisis Context - Aurica Dvoracic (CES Working Papers, 2015)
It suffices to browse the websites of only a few of the most noteworthy Romanian cultural organizations – including the website of the Ministry of Culture – to conclude that quality policies are missing. In fact, these are not the only policies that are missing, but this topic should be discussed in another paper. The objective of this paper is to analyze the progresses and the opportunities, as well as the problems and the challenges that the Romanian society and economy are facing as far as culture is concerned at the beginning of the new millennium, in the particular context of the global economic crisis: specifically, we will focus on the role of cultural organization managers in implementing quality management as the main factor in assuring the competitiveness needed to overcome the crisis. Cultural organization managers generally admit that a change is needed in order to cope with competitive pressure, but few understand how this change should be implemented. To avoid the issues associated with “change programs”, the management of cultural organizations must focus on the structure of processes, recognizing the roles and responsibilities of their employees in the processes in which they are involved.
Keywords: G01; Z19; 330; quality management; culture; cultural organizations; consumer; cultural services; competitiveness; global economic crisis